Applications of neural-type structured networks for solving algebraic matrix equations and computation of the Drazin inverse - Cichocki, Andrzej; Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
An overview of the methods of solving algebraic matrix equations and computation of the Drazin inverse of a singular matrix with the use of neural-type structured networks is presented.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka